The problem of evil and moral indifference - Mawson, T (Cambridge University Press, 1999)
In this paper, I argue that if the libertarian free will defence were seen to fail because determinism were seen to be true, then another solution to the problem of evil would present itself. I start by arguing that one cannot, by consideration of agents' choices between morally indifferent options, reach any conclusion as to those agents' moral qualities. If certain forms of consequentialism were false, determinism true, and if there were a God who chose to create this universe, then His choice would have been between such options. Consideration of the general nature of the universe God putatively chose to create would not then license any conclusion as His moral qualities.